ВРАХУВАННЯ ОСОБЛИВОСТЕЙ БІОІМПЕДАНСУ ПРИ ВИСОКИХ ЧАСТОТАХ МОДЕЛЯМИ ФРІКЕ ТА КОУЛА - Сидорець, В.М.; Пентегов, І.В.; Римар, С.В. (Інститут електродинаміки НАН України, Київ, 2018)
The principles have been analyzed that were used to create models of biological tissues describing the phenomenon of bioimpedance dispersion, i.e., the laws of its dependence on frequency. The advantages and disadvantages of the Fricke and Cole models are determined, as well as the frequency ranges in which they yield results that coincide with the experiment. It is shown that the Fricke model is more promising for its adaptation in the high-frequency region, where βdispersion is observed. In this case, it becomes possible to use it to monitor the state of biological tissue during highfrequency electrosurgical interventions. References 10, figures 2.